Peran Pemerintah Daerah Dalam Pelaksanaan Pemerintahan Yang Baik (Good Governance) Dibidang Pembinaan Dan Pengawasan Indikasi Geografis - Aridhayandi, M. Rendi (Jurnal Hukum & Pembangunan, 2018)
The Regional Government is the regional head as an element of the Regional Government organizing the execution of government affairs which is the authority of the autonomous regions. In the implementation of government affairs must implement the principles of good governance. One of the roles of Regional Government is in the field of guidance and supervision of Geographical Indication in accordance with the mandate of Articles 70 and 71 Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis. This is important in legal protection of products that are characterized by the geographic area of a region, only in the area and not owned in other areas. This becomes an asset area that can be useful for the welfare of the community, especially farmers.